2018
DOI: 10.3233/jad-171093
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Aggregated Analysis on the Impact of Amyloid PET Brain Imaging on the Diagnosis, Diagnostic Confidence, and Management of Patients being Evaluated for Alzheimer’s Disease

Abstract: Background:Amyloid PET (aPET) imaging could improve patient outcomes in clinical practice, but the extent of impact needs quantification.Objective:To provide an aggregated quantitative analysis of the value added by aPET in cognitively impaired subjects.Methods:Systematic literature searches were performed in Embase and Medline until January 2017. 1,531 cases over 12 studies were included (1,142 cases over seven studies in the primary analysis where aPET was the key biomarker; the remaining cases included as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 60 publications
2
52
0
1
Order By: Relevance
“…First, the nonrandomized design and lack of a control group limit the direct attribution of changes in management to PET. However, the rates of changes in management were similar to those reported in randomized studies, 20,21 and physicians ascribed a large majority of all changes to the scan results. Second, patients were in-cluded in the study based on criteria that "knowledge of PET results is expected to change diagnosis and management."…”
Section: Limitationssupporting
confidence: 72%
See 1 more Smart Citation
“…First, the nonrandomized design and lack of a control group limit the direct attribution of changes in management to PET. However, the rates of changes in management were similar to those reported in randomized studies, 20,21 and physicians ascribed a large majority of all changes to the scan results. Second, patients were in-cluded in the study based on criteria that "knowledge of PET results is expected to change diagnosis and management."…”
Section: Limitationssupporting
confidence: 72%
“…16 Rates of change in both groups were significantly higher than the a priori target threshold of 30% and were comparable to results reported in smaller studies and recent meta-analyses. [20][21][22] The most frequent change in management involved the use of Alzheimer disease drugs, the aspect of management most directly tied to etiologic diagnosis. Cholinesterase inhibitors and memantine are approved for the symptomatic treatment of Alzheimer disease, 23 and cholinesterase inhibitors also show some efficacy in the treatment of dementia with Lewy bodies and Parkinson disease dementia, 24 conditions that often involve amyloid deposition.…”
Section: Discussionmentioning
confidence: 99%
“…In a larger cohort analysis, Beach et al [ 17 ] similarly found discordance between a clinical diagnosis of AD and an absence of amyloid pathology at autopsy in up to 30% of patients. Additionally, in a recent meta-analysis Fantoni et al [ 18 ] found that just over 30% of patients with a diagnosis of AD on presentation had AD ruled out by a negative amyloid PET result, and a similar figure of 29% was found by Barthel and Sabri [ 19 ]. These findings indicate that the work-up of the AD patient could be improved by the presence of biomarker data in the form of an amyloid PET scan [ 20 ].…”
Section: Discussionmentioning
confidence: 72%
“…The imaging biomarkers groups extended the previous consensus work, 4,63 by incorporating new research published since 2012 especially systematic reviews and meta-analyses, [64][65][66][67][68][69][70][71][72][73] and guidelines and task force documents. [74][75][76][77][78][79][80][81][82][83] We have refined our suggestions on the (Table 4).…”
Section: Use Of Neuroimaging and Fluid Biomarkersmentioning
confidence: 99%